KEMAMPUAN TEKNIK DASAR BULUTANGKIS PADA ATLET PEMULA DI ASJAD CLUB PONTIANAK - Asrofi Asrofi; Fitriana Puspa Hidasari; Mimi Haetami (Universitas Tanjungpura, 2021)
AbstractThe background of this research is the formulation of the problem, namely how the ability of basic badminton techniques for beginners at Asjad Club Pontianak. The goal to be achieved is to determine the basic technical ability of badminton in beginner athletes at Asjad Club Pontianak. The research method used is descriptive quantitative method in the form of survey research. The sample used in this study were 30 beginner athletes at Asjad Club Pontianak.Based on the results of the research that has been carried out, the value of 30 athletes for long service obtained an average value of 46.47, while in the good category as many as 22 athletes with a percentage of 73.33% and 8 athletes can be categorized as sufficient with a percentage of 26.67%. The backhand short serve value obtained an average value of 52.33 and from 30 athletes all of them could be categorized as good with a percentage of 100%. The average value for the basic technical ability of badminton over lob obtained an average value of 52.37 with a good category obtained by 26 athletes with a percentage of 86.67%, a sufficient category with a percentage of 6.67% with 2 athletes and for the very good category a percentage value of 6.67% with 2 athletes. As for the value of basic smash ability, the average value is 56.70 with a sufficient category obtained by 2 athletes with a percentage of 6.67% and a good category obtained a percentage of 93.33% with 28 novice athletes at Asjad Club Pontianak. The results of the research above can be concluded that the overall basic technical ability of badminton in 30 beginner athletes at Asjad Club Pontianak can be categorized as good.Keywords: Basic Technique Ability, Badminton Strokean